Conflicts between informative self-determination and profile segmentation through online programmatic advertising in Peru - Sosa Huapaya, Alex (2024)
The purpose of this paper is to analyze the effects on the right to informational self-determination that can arise due to the use of online behavioral programmatic advertising as a tool for customer profiling and segmentation. In this research, the dogmatic method is used in order to analyze programmatic advertising regarding freedom of information protected in the Peruvian constitution, the rules that regulate its effects and pronouncements from the National Personal Data Authority, Indecopi, as well as European legislation. Thus, it aims to conclude if Peruvian regulations are appropriate to establish reasonable limits to this advertising strategy.